2021
DOI: 10.1051/matecconf/202133609001
|View full text |Cite
|
Sign up to set email alerts
|

Research on recycling channel selection of closed-loop supply chain considering consumer preference and fairness concern

Abstract: This paper studied the influence of consumer preference and fairness concern on recycling and pricing decisions of closed-loop supply chain (CLSC) under different recycling channels. The results show that consumers' fairness concern cannot affect the manufacturer's decisions and profit; consumers' fairness concern is benefit to consumers, and it can improve the recycle rate. The channel selection strategy is depend on consumers' fairness attitude.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…In reference to the impact of recycling channels on closed-loop supply chains, Li et al designed three recycling channel decision models for retailers, manufacturers, and dual recycling, and analyzed and discussed the impact of manufacturers' fairness preference on closed-loop supply chain decisions under different recycling channels [32]. In their study on the impact of consumer preferences on closed-loop supply chains, Sun et al constructed single-channel and dual-channel closed-loop supply chain decision-making models to explore the impact of consumers' remanufactured product preferences and fairness concerns on members' decision-making and profits, and found that with the increase of consumers' remanufactured product preferences, manufacturers' and retailers' profits and waste product recovery rates increased [33]. In regard to the impact of Corporate Social Responsibility (CSR) on closed-loop supply chains, Yan et al considered a closed-loop supply chain system with CSR awareness, and found that manufacturers' CSR awareness and retailers' CSR investment have mutual incentives, and with the enhancement of manufacturers' CSR awareness, the total profits of the closed-loop supply chain under the four main enterprise strategy models increase [34].…”
Section: Study On the Influence Of Internal And External Factors On C...mentioning
confidence: 99%
See 1 more Smart Citation
“…In reference to the impact of recycling channels on closed-loop supply chains, Li et al designed three recycling channel decision models for retailers, manufacturers, and dual recycling, and analyzed and discussed the impact of manufacturers' fairness preference on closed-loop supply chain decisions under different recycling channels [32]. In their study on the impact of consumer preferences on closed-loop supply chains, Sun et al constructed single-channel and dual-channel closed-loop supply chain decision-making models to explore the impact of consumers' remanufactured product preferences and fairness concerns on members' decision-making and profits, and found that with the increase of consumers' remanufactured product preferences, manufacturers' and retailers' profits and waste product recovery rates increased [33]. In regard to the impact of Corporate Social Responsibility (CSR) on closed-loop supply chains, Yan et al considered a closed-loop supply chain system with CSR awareness, and found that manufacturers' CSR awareness and retailers' CSR investment have mutual incentives, and with the enhancement of manufacturers' CSR awareness, the total profits of the closed-loop supply chain under the four main enterprise strategy models increase [34].…”
Section: Study On the Influence Of Internal And External Factors On C...mentioning
confidence: 99%
“…Although there are many studies that explore the impact of internal and external factors on closed-loop supply chain systems, few have studied the impact of external raw material supply on component remanufacturing or closed-loop supply chain systems, such as new parts required for component remanufacturing. The existing studies focus on reflecting the operation advantages and disadvantages of closed-loop supply chain systems from the perspective of profit acquisition ability, for example, literature [30,33,34,39] However, the existing works rarely analyze the system operation from multiple perspectives. At the same time, the above literature also ignores the dynamic adjustment of government reward and punishment strategies when considering government reward and punishment strategies, for example, literature [36,37].…”
Section: Study On the Influence Of Internal And External Factors On C...mentioning
confidence: 99%
“…Hong et al concluded from their study that the degree of consumer preference for remanufactured products affects the price of remanufactured products at wholesale, retail and recycling, and that the recycling price increases with the increase in wholesale and retail prices [3] . Sun et al develop but-channel and dual-channel closed-loop supply chain models based on consumer preferences and consumer equity concerns to discuss the impact of consumer acceptance of remanufactured goods and equity concerns on members' decisions and profits [9] . For the quality of raw materials in the recycling process, Feng et al construct a multi-level competitive recycling and remanufacturing supply chain game model with two manufacturers and multiple recyclers to analyze the pricing coordination problem [2] .…”
Section: Introductionmentioning
confidence: 99%